Analysis of 5 MW Blade Two-Way Fluid-Structure Interaction Characteristics. (1st March 2023) - Lin, Xihan; Liu, Jiang; Jiang, Weiting; Fu, Zaiguo
Abstract: A CFD-CSD coupled method was employed to establish an aeroelastic model of the NREL 5 MW wind turbine. The two-way fluid-structure interaction (FSI) simulation was carried out for this aeroelastic model. The response curves of blade tip flapwise, edgewise, and torsional deformation under normal operating conditions was obtained. The results show that the blade deformation shows a trend of increasing and then decreasing from the cut-in wind speed to the cut-out wind speed with the rise in wind speed. The maximum deformation appears in the vicinity of rated working conditions. Furthermore, the difference in aerodynamic performance between two-way FSI and one-way FSI has been studied to reveal the influence of the aeroelastic effect on performance. The two-way FSI that considers the blade deformation causes significant periodic fluctuations in the torque and thrust curves, with a maximum deviation of 3.75% in the average torque at 20 m/s. Therefore, the two-way FSI that introduces the aeroelastic effect can predict the aerodynamic performance more accurately.